Experimental Study on Outdoor Heat Exchanger Frosting Characteristics of a Heat Pump Air-conditioning System for Electric Vehicles - Bao Jiaqian; Su Lin; Liu Mingkang; Fang Yidong; Li Kang (Zhileng xuebao)
Exterior heat exchangers of heat pumps in electric vehicles are prone to frost when operated in winter. This project experimentally investigated this phenomenon. A relationship between frost growth and reductions in the surface temperature of the external heat exchanger was demonstrated. Furthermore, the distribution of frost on each flow channel was uneven, reflecting the different refrigerant densities of gaseous and liquid phases within the channel and the influence of gravity, which leads to a separation and uneven distribution of the two-phase refrigerant in the flow channel. In addition, the increase of frost on the exterior heat exchanger will result in decreased refrigerant temperature within the exterior heat exchanger, and decreased suction and discharge pressures of the compressor and heating capacity, while causing an increased unit power consumption of the compressor. With an ambient temperature of 0 °C, when the rate of frost coverage reaches 77.4%, the reduction of suction pressure, discharge pressure, and heating capacity were 33.4%, 12.1%, and 25.8%, respectively. Further, the increase of unit power consumption was 32.0%, which reduced the stability of operation and led to an unacceptable level of heating.